Revitalisasi Tradisi Jamasan Pada Era Modernisasi di Desa Dawuhan, Banyumas - Burhannurdin Nabih Kurniawan; Sentot Satrio Wibisono; Nailatul Muna; Ernawati Ernawati; Diadjeng Sekar Pradianda; Shinta Dewi Agustina; Niken Pararmarti Dasuki (Universitas Lambung Mangkurat, 2025)
The advent of modernization has led to the gradual neglect of local traditions, as people today are more focused on technological advancements and modern lifestyles, which are considered more practical and efficient. The Jamasan tradition in Dawuhan Village, Banyumas Regency, is a significant part of the local community's life, where villagers gather to clean sacred heirlooms and preserve ancestral values. However, with the passage of time, villagers spend more time with technology and other modern activities, causing cultural heritage like Jamasan to be sidelined. This research aims to identify how revitalization and strategies are applied to ensure the sustainability of the Jamasan tradition so that it remains relevant in the modern era. The researcher applied purposive sampling techniques to select informants who met the research criteria. Data was collected through in-depth interviews, direct observation, and literature studies to gain a comprehensive understanding. The research findings reveal efforts to increase community participation in the Jamasan tradition through a series of events called Kalibening Culture Heritage. These activities include various traditional art performances, such as stage performances and religious events, which encourage active community participation. The strategy to enliven this event includes promotion on social media platforms like Facebook, Instagram, and WhatsApp. As we know, people are inseparable from their gadgets, making social media dissemination an appropriate strategy. These activities have increased the interest of the younger generation and village residents in appreciating and preserving their cultural heritage